2020
DOI: 10.1038/s41598-020-77183-y
|View full text |Cite
|
Sign up to set email alerts
|

The optimal alternative for quantifying reference evapotranspiration in climatic sub-regions of Bangladesh

Abstract: Reference evapotranspiration (ETo) is a basic element for hydrological designing and agricultural water resources management. The FAO56 recommended Penman–Monteith (FAO56-PM) formula recognized worldwide as the robust and standard model for calculating ETo. However, the use of the FAO56-PM model is restricted in some data-scarce regions like Bangladesh. Therefore, it is imperative to find an optimal alternative for estimating ETo against FAO56-PM model. This study comprehensively compared the performance of 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 72 publications
3
19
1
Order By: Relevance
“…Different studies [63][64][65] observed good results for Rs estimates using Equation (3); however, there is a lack of studies about solar radiation estimates in the Brazilian Cerrado. Other authors reported better performance of ETo calculated with estimated Rs [36][37][38]61,[66][67][68] than observed here, and ETo highly correlated with solar radiation in several different locations [25,27,69,70]. More research is needed to find a better model for estimating Rs and Rn.…”
Section: Et O Estimates With Limited Climatic Datacontrasting
confidence: 48%
“…Different studies [63][64][65] observed good results for Rs estimates using Equation (3); however, there is a lack of studies about solar radiation estimates in the Brazilian Cerrado. Other authors reported better performance of ETo calculated with estimated Rs [36][37][38]61,[66][67][68] than observed here, and ETo highly correlated with solar radiation in several different locations [25,27,69,70]. More research is needed to find a better model for estimating Rs and Rn.…”
Section: Et O Estimates With Limited Climatic Datacontrasting
confidence: 48%
“…Although many researchers have investigated the changes and variabilities of Bangladesh’s climate at the regional and country levels (Islam et al 2017 , 2020 ; Salam et al 2020 ), the climate-health relationship studies in the country are very rare (Rahman et al 2019 ; Nissan et al 2020 ). The previous studies are focused mainly on HI anomaly assessment (Rajib et al 2011 ), extreme temperature variability (Rakib 2013 ), HI trends in southwest Bangladesh (Rakib 2018 ), effects of heat extreme (Burkart et al 2014 ), mortality due to high temperature (Burkart et al 2011 ), and heatwave prediction (Nissan et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Luab et al analyzed the changing characteristics and influencing factors of evapotranspiration and demonstrated evapotranspiration trends in different seasons by using the multiple linear regression analysis method and the main factor weighted comprehensive 22 . To date, relevant studies have focused on the temporal and spatial evolution trends of evapotranspiration, the ecological elements that affect the change in evapotranspiration, and the correlations between evapotranspiration and meteorological factors 23,24 . Additionally, drought and water shortages are the main challenges to resources and ecology and climate change will have a great impact on the hydrology of a region 16 .…”
mentioning
confidence: 99%